Emergency Preparedness and Response Assessment : Albania - World Bank (World Bank, Washington, DC, 2021)
The ready2respond (R2R) framework was developed in reference to the role of the World Bank in disaster risk reduction (DRR). While strengthening emergency preparedness and response (EP and R) is a sound investment on its own, it also supports the World Bank Group’s broader risk reduction efforts and its fundamental goal of eliminating poverty and promoting shared prosperity. This report includes the assessment of the EP and R capacities of Albania based on the R2R diagnostic methodology, as designed by the World Bank and executed by prepared international (PPI). Data from a desk review and from key informant interviews conducted as part of an online field mission generated findings on the five components of the diagnostic - legal and institutional frameworks, information, facilities, equipment, and personnel - which include 18 criteria, 72 indicators, and 360 attributes in total. This report provides a summary of the EP and R capacities per component, as assessed by PPI in the first half of 2020; the full assessment report, structured in accordance with the R2R methodology, can be found in annex 1. The report also identifies and makes recommendations about key investments that the World Bank and other stakeholders can consider as they seek to strengthen EP and R capacities in Albania.